Changes in take-home aerated soft drink purchases in urban India after the implementation of Goods and Services Tax (GST): An interrupted time series analysis. (June 2021) - Law, Cherry; Brown, Kerry Ann; Green, Rosemary; Venkateshmurthy, Nikhil Srinivasapura; Mohan, Sailesh; Scheelbeek, Pauline F.D.; Shankar, Bhavani; Dangour, Alan D.; Cornelsen, Laura
Abstract: Objectives: Taxes on sugar-sweetened beverages (SSB) are increasingly being implemented as public health interventions to limit the consumption of sugar and reduce associated health risks. In July 2017, India imposed a new tax rate on aerated (carbonated) drinks as part of the Goods and Services Tax (GST) reform. This study investigates the post-GST changes in the purchase of aerated drinks in urban India. Methods: An interrupted time series analysis was conducted on state-level monthly take-home purchases of aerated drinks in urban India from January 2013 to June 2018. We assessed changes in the year-on-year growth rate (i.e. percentage change) in aerated drink purchases with controls for contextual variables. Results: We found no evidence of a reduction in state-level monthly take-home aerated drink purchases in urban India following the implementation of GST. Further analysis showed that the year-on-year growth rate in aerated drink purchases increased slightly (0.1 percentage point per month, 95%CI = 0.018, 0.181) after the implementation of GST; however, this trend was temporary and decreased over time (0.008 percentage point per month, 95%CI = −0.015, −0.001). Conclusions: In India, a country currently with low aerated drink consumption, the implementation of GST was not associated with a reduction in aerated drink purchase in urban settings. Due to the lack of accurate and sufficiently detailed price data, it is not possible to say whether this finding is driven by prices not changing sufficiently. Furthermore, the impact of GST reform on industry practice (reformulation, marketing) and individual behaviour choices (substitution) is unknown and warrants further investigation to understand how such taxes could be implemented to deliver public health benefits. Highlights: India imposed a new tax rate on aerated drinks as part of the GST reform in 2017. We study changes in aerated drink purchases in urban India from 2013 to 2018. No evidence for post-GST decrease in state-level monthly take-home drink purchases. Need further research to identify the reasons behind the post-GST purchase trend.